Islamic critical thinking on the thematic unity of al-Qur’ān in Al-Asās Fī At-Tafsīr - Mutammimul Ula, Maryam Qonitat; Elatrash, Radwan Jamal Yousef (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study aims to explain a brief biography of Said Hawwa, one of prominent and influential Islamic scholar that lived in 19th century, and to analyse his book which titled Al-Asās fī Tafsīr from the critical thinking perspective. To obtain the result, the writer use two methods; descriptive method and analytical method. The first method used to collect informations regarding a whole brief life of Said Hawwa and his works, as well as informations regarding the methodology that used by Said hawwa in his book Al-Asās fī Tafsīr. The second method used to analyse the concept, theories of unity of theme in Al-Qur’ān which was iniated by Said Hawwa, and to analyse its theories based on critical thinking perspective as islamic scholar. By these two methods, the writer found that according to him, there are two parts unity thematic of Al-Qur’ān. First, the unity thematic in every Sūrah of Al-qur’ān, which detailed the unity into each āyah, each beginning, and each ending. Second, the unity thematic of Al-Qur’ān in general which centered from Al-Baqoroh as the main sūrah in Al-Qur’ān. These unity of theme resulted in a great coherent of Al-Qur’ān. **************************************************************************** تهدف هذه الدراسة إلى شرح موجز عن سيرة سعيد حوى، أحد العلماء البارزين الذي عاش في القرن التاسع عشر، ولتحليل كتابه في التفسير بعنوان الأساس في التفسير من منظور التفكير النقدي. وللحصول على النتيجة، تستخدم الباحثة بالمنهجين الأساسين؛ المنهج الإستقرائي والمنهج التحليلي. أما المنهج الإستقرائي تستخدم لجمع المعلومات المتعلقة بحياة قصيرة من سعيد حوى وأعماله، وكذلك المعلومات المتعلقة بالمنهجية التي استخدمها سعيد حوى في كتابه الأساس في التفسير. وأما المنهج التحليلي تستخدم لتحليل المفهوم، ونظريات حول وحدة الموضوع في القرآن التي قام بها سعيد حوى، وتحليل نظرياتها على أساس منظور التفكير النقدي كعالم إسلامي. من خلال هاذين منهجين، وجدت الباحثة أن هناك قسمان كبيران في الوحدة الموضوعية للقرآن. أولاً: الوحدة الموضوعية في كل سورة القرآن، التي تفصّل الوحدة في كل منها، كل بداية وكل نهاية. ثانياً، الوحدة الموضوعية للقرآن بشكل عام التي تتركز في سورة البقرة كمنطلق رئيسي في القرآن. هذه الوحدة من الموضوعات في القرآن دلت على شمولية الموضوع في القرآن.